2019
DOI: 10.3390/su11102946
|View full text |Cite
|
Sign up to set email alerts
|

The Interdependence of Debt and Innovation Sustainability: Evidence from the Onset of Credit Default Swaps

Abstract: Innovation sustainability requires sustainable financing. Extensive research suggests that debt is a disfavored source of innovation financing. In this study, we show that a recent financial development, credit default swaps (CDSs), may change the institutional logics of debt, making debt useful to the financing innovation. To be specific, we find that with CDS protection, creditors become less concerned with a borrowing firm’s credit risk and risk taking, making debt tolerant of early failures and reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Debt, then, becomes a stimulus to investment (Choi et al, 2016; García‐Pérez et al, 2013; Wu et al, 2016). In addition, when debt costs are lower, companies have greater possibilities to innovate (Chen & Zhang, 2019). The influence of debt terms is greater for more innovative companies (Sun, 2020), which is accentuated even further in SMEs (Gorodnichenko & Schnitzer, 2013).…”
Section: Literature Review and Hypotheses Proposedmentioning
confidence: 99%
See 1 more Smart Citation
“…Debt, then, becomes a stimulus to investment (Choi et al, 2016; García‐Pérez et al, 2013; Wu et al, 2016). In addition, when debt costs are lower, companies have greater possibilities to innovate (Chen & Zhang, 2019). The influence of debt terms is greater for more innovative companies (Sun, 2020), which is accentuated even further in SMEs (Gorodnichenko & Schnitzer, 2013).…”
Section: Literature Review and Hypotheses Proposedmentioning
confidence: 99%
“…The better the debt terms are, the greater a firm's capacity to innovate will be (Wu et al, 2016). In addition, due to its risk and cost (Chen & Zhang, 2019; Rangel, 2012), debt becomes an essential instrument to steer innovation to its optimum level (Choi et al, 2016). Investment in innovation represents a bet on the future, which can generate uncertainty (Ayalew & Xianzhi, 2019).…”
Section: Literature Review and Hypotheses Proposedmentioning
confidence: 99%
“…Similarly, by applying OLS methods, Breuer [ 28 ] concluded that there is a positive association between capital allocations and the legal protection of minority investors. Using a panel approach, Chen et al [ 29 ] highlighted the significance of institutions for credit cycles. They learned that improvements in operative creditor rights led to a decrease in the volatility of the credit cycle.…”
Section: Literature Reviewmentioning
confidence: 99%